(untitled) (Academia Science Repository, 2023)
In this article, the issue of making the movement of material flows, i.e. finished products, raw materials, fuel resources, building materials, agricultural products, waste of production activities, etc., in space through the shortest distance, at the lowest cost was considered. Optimization of raw materials or semi-finished product flows that need to be transported allows you to determine the plan that provides the minimum of the transport work being carried out.